SISTEM MONITORING DAN EVALUASI NILAI SISWA BERBASIS DASHBOARD BERDASARKAN KEY PERFORMANCE INDICATOR (STUDI KASUS : SMP KARTIKA II-2 BANDARLAMPUNG) - Ahmad Syihabuddin; Zaenal Abidin (Universitas Teknokrat Indonesia, 2020)
Abstract – In the world of education, every school must have a good, quality and national standard teaching system. This step can be achieved by learning to make annual repairs and evaluations such as Bandar Kartika II Junior High School. The evaluation process is carried out by the teacher and the school curriculum development team which is conducted every semester. This step starts by collecting all student data from learning grades to non-academic activities. These data are scattered in the form of excel documents or homeroom records used as information. Information is obtained from operators who play a role in gathering all data for curriculum meeting decisions. The process of collecting data often experiences obstacles such as incorrect data entry, copy and paste data from teachers often error when inputted on the application value operator. Still have to be verified manually by curriculum sections and large program sizes that require high specifications on a PC or laptop. Not all teachers provide complete information for non-academic assessments. Then the evaluation process always does not have accurate data, especially the operator must wait for completing the evaluation recap.The application of monitoring and evaluating student grades is done by the assessment method using KPI (Key Performance Indicator) with the weight of the assessment that has been set by the school and has 3 assessments namely Tests, Measurements, and Assessments. Designed using UML (Unifield Modeling Language), Usecase Diagrams, Activity Diagrams, and Prototyping as a system development method, based on the results of implementation carried out with the application of testing using ISO / IEC 25010 Quality in Use Model (Usability) obtained 88% and 83% results for testing functionality so that the system can be concluded to be feasible to use. Key words: Monitoring System, Evaluation of Value, Students, Dashboard, Key Performance Indicator